2021
DOI: 10.21608/ejchem.2021.30318.2648
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics studies on the adsorption of phenol from aqueous solution by coffee husk activated carbon

Abstract: Activated carbons (ACs) obtained from coffee husk by KOH activation at 650 (ACK-650) and 750 o C (ACK-750), were used as an adsorbent for the adsorption of phenol from aqueous solution. The ACs was characterized by SEM, EDX, BET, and Boehm titration techniques. The experimental equilibrium data of phenol adsorption was analyzed by eight isotherm models, which are four two-parameter equations (Langmuir, Freundlich, Elovich, and Temkin) and four three-parameter equations (Redlich-Peterson, Sips, Radke-Prausnitz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…At low adsorbate concentrations, the Sips model reduces to the Freundlich model, and at high concentrations, it predicts monolayer formation, which is characteristic of the Langmuir isotherm. Kamiński et al (2020) and Ta et al (2021) also demonstrated that the Sips model was more suitable for representing phenol adsorption equilibrium data using activated carbons.…”
Section: Equilibrium Isotherms Of Phenol Adsorption Onto the Acsmentioning
confidence: 95%
“…At low adsorbate concentrations, the Sips model reduces to the Freundlich model, and at high concentrations, it predicts monolayer formation, which is characteristic of the Langmuir isotherm. Kamiński et al (2020) and Ta et al (2021) also demonstrated that the Sips model was more suitable for representing phenol adsorption equilibrium data using activated carbons.…”
Section: Equilibrium Isotherms Of Phenol Adsorption Onto the Acsmentioning
confidence: 95%